Oxidative Stress in Aquatic Organisms - Changyou Song; Cunxin Sun; Bo Liu; Pao Xu (MDPI AG, 2023)
Oxidative stress mainly refers to the imbalance between reactive oxygen species production and antioxidant defense systems in organisms [...]